Analysis of the Influence of Regional Tax Fund Allocation on the Quality of Road Infrastructure in Medan City - Farazqy Adrian, Muhammad (Yayasan Mentari Madani, 2024)
This study aims to analyze the influence of regional tax fund allocation on the quality of road infrastructure in Medan City. With the need for infrastructure increasing in line with economic growth and population density, this study identifies the extent to which the allocation of local tax funds affects road repair and maintenance, as well as other factors that play a role in the effective use of these funds. The methodology used includes regression analysis to evaluate the relationship between fund allocation, economic growth, number of vehicles, and population density on road quality. The results showed that the allocation of regional tax funds had a significant and positive influence on the quality of road infrastructure with a regression coefficient of 0.45 (p < 0.05), indicating that a 1% increase in fund allocation was related to an increase in the road quality index by 0.45 points. In addition, economic growth also has a positive effect (coefficient 0.30), while the number of vehicles (-0.20) and population density (-0.25) have a negative impact on road quality. These findings show that consistent allocation of funds and long-term planning that takes into account economic and social factors are essential for the improvement of road infrastructure. This study recommends increasing the allocation of local tax funds, better budget planning, and the application of technology for road monitoring and maintenance. The implementation of this recommendation is expected to improve the quality of life of the community and encourage economic growth in the city of Medan